The Possible Link Between Manufacturing and Probiotic Efficacy; a Molecular Point of View on Bifidobacterium - Duboux, Stéphane; Van Wijchen, Myrthe; Kleerebezem, Michiel (Frontiers in Microbiology, 2021)
Probiotics for food or supplement use have been studied in numerous clinical trials, addressing a broad variety of diseases and conditions. However, discrepancies were observed in the clinical outcomes stemming from the use of lactobacillaceae and bifidobacteria strains. These differences are often attributed to variations in the clinical trial protocol like trial design, included target population, probiotic dosage, or outcome parameters measured. However, a contribution of the methods used to produce the live bioactive ingredients should not be neglected as a possible additional factor in the observed clinical outcome variations. It is well established that manufacturing conditions play a role in determining the survival and viability of probiotics, but much less is known about their influence on the probiotic molecular composition and functionality. In this review, we briefly summarize the evidence obtained for Lacticaseibacillus rhamnosus GG and Lactiplantibacillus plantarum WCFS1, highlighting that expression and presence of probiotic niche factor (NF) and/or effector molecules (EM) may be altered during production of those two well-characterized lactobacillaceae probiotic strains. Subsequently, we summarize in more depth what is the present state of knowledge about bifidobacterial probiotic NF and EM; how their expression may be modified by manufacturing related environmental factors and how that may affect their biological activity in the host. This review highlights the importance of gathering knowledge on probiotic NF and EM, to validate them as surrogate markers of probiotic functionality. We further propose that monitoring of validated NF and/or EM during production and/or in the final preparation could complement viable count assessments that are currently applied in industry. Overall, we suggest that implementation of molecular level quality controls (i.e., based on validated NF and EM), could provide mode of action based in vitro tests contributing to better control the health-promoting reliability of probiotic products.